Disparidades e persistência do desemprego regional no Brasil - Ferrari, Tatiana Kolodin (2012)
This study aimed to analyze the behavior of regional unemployment rates in Brazil. In particular, it attempted to identify the existence of a process of convergence and if it is characterized as conditional or unconditional. The main innovation is to extending this type of analysis for the 27 Federal Units. Using panel unit-root tests, we can strongly reject the unit-root hypothesis, suggesting that shocks to regional unemployment rates have transitory effects and the convergence is characterized as conditional, which explains the existence of stable differences among regional unemployment rates. The evidences align with the equilibrium approach or compensatory theory, which explains the phenomenon as an individual preference for certain areas.